Home Surveillance Monitoring with Esp32-Cam and SD Card For Data Storage - Tirta, Ivan Danu; Wisaksono, Arief; Ahfas, Akhmad; Jamaaluddin, Jamaaluddin (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
In the last three years the crime rate of theft has increased, to reduce crime this form of theft can be overcome by making a home security system using ESP32-CAM, the system made aims to conduct surveillance that can be seen again the results of images that have been taken by ESP32-CAM, then stored on the SD Card and send notifications to social media. This research uses the R&D (Research &; Development) method or research, and development is a systematic study process to develop and validate products to be used in education. Products developed / produced include training materials for teachers, teaching materials, learning media, questions, and management systems in learning. The result of the implementation of a security system is the stage where the system that has been designed explains the creation of a system in accordance with previous analysis and design. After the implementation stage is carried out, a system test is needed to prove that the application can run properly. The test results that have been done using the android application and Sdcard run well, the PIR sensor can only detect objects as far as 4 meters. With this system, it is expected to be able to provide protection and security for homes, property, and residents. On the other hand, this approach also creates a chance to dig deeper into technology development using ESP32-CAM as an effective and efficient solution to tackle rising crime.